Amaryllidaceae endémicas del Perú - León, Blanca (2006)
The Amaryllidaceae are one of the most interesting families because of adaptations of many species to xeric environments. Twenty-four genera and 138 species, all of them herbaceous are known from Peru (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we report 54 endemic taxa in 15 genera, including «amancaes» (Ismene amancaes). This family includes one genus endemic to Peru, Rauhia. Endemic taxa are found in several ecological regions, including both Humid Montane and Premontane Forests, between 100 and 4700 m elevation. More than half of the species are known from a single locality, these are generally in poorly-explored non-forested environments. Just four Amaryllidaceae species endemic to Peru have been recorded within the country’s protected area network